Anthrax Outbreak of Ostrich Farm in The Regency of Purwakarta, West Java, Indonesia - Hardjoutomo, Suprodjo; Poerwadikarta, M Bhakti; Barkah, Koko (Indonesian Bulletin of Animal and Veterinary Sciences, 2002)
An anthrax outbreak in ostrich farm in the Regency of Purwakarta, West Java occurred in late of 1999. It is belived that the case as the first reported anthrax outbreak of ostrich in Indonesia. A total number of 254 head of ostriches have had succumbed of the disease and the death of ostriches has actually been commenced in August, 1999 until December, 1999. The anthrax diagnosis has been confirmed laboratorically by the Research Institute for Veterinary Science (RIVS), Bogor, West Java. It was found that 59 out of 130 pieces of processed ostrich skin samples were positive Bacillus anthracis. Whereas, 4 soil samples and 37 frozen meats offals and body fat samples were all negative. In parallel of the outbreak of anthrax in Purwakarta, special action have to be forced into the community as far as the veterinary policy of the Republic of Indonesia in concerned. Â  Key words: Anthrax, ostrich, Purwakarta, outbreak